(untitled) (Linguamática, 2013)
The objectives of this study are as follows: to present a methodology for the development of a lexical resource with semantic information; to compare semantic roles in specialized and non-specialized language; and to observe the semantic role labeling (SRL) made by a group of annotators. Two experiments revolving around SRL in Portuguese were developed: a comparison between data in specialized and non-specialized language corpora; and an annotation evaluation for verifying the agreement among multiple annotators for the task of SRL. As for results, a qualitative difference between the corpora was observed, and the most prominent feature was the omission of agents in specialized texts. There was little agreement among annotators, which points toward the necessity of more training, or a simplification of the task, which does not seem to be possible at this stage of development.